PTSD assistance dogs: concerns for animal well-being, rights, and justice - Kiiroja, Laura; Gadbois, Simon; Fenton, Andrew (Frontiers in Veterinary Science, 2025)
PTSD assistance dogs are service dogs trained to assist individuals living with PTSD. A growing body of research links the use of PTSD assistance dogs with substantial benefits for their human partners, including significant reductions in PTSD symptoms, and improvements in family functioning, social integration, and quality of life. However, research on the effect of assistance work on PTSD assistance dogs themselves is notably lacking. This paper aims to address this gap by mapping potential animal welfare and ethical concerns associated with PTSD assistance dog interventions. Moreover, a rights-oriented approach is employed, with the aim of suggesting guidelines that promote interspecies justice and contribute to the dogs’ well-being. The discussion highlights significant welfare concerns due to the lack of standardisation in the selection, rearing, training, and follow-up care of PTSD assistance dogs. Some of the symptoms and comorbidities common in people with PTSD (e.g., dysregulated anger, substance use disorder), along with some trained tasks of the dogs (e.g., diffusing the human’s episodes of distress/anger and interrupting flashbacks/nightmares), further exacerbate these concerns. PTSD assistance dogs also share a number of potential welfare issues with other assistance dogs, such as disruption of close relationships, lack of control over their physical and social environment, and insufficient down-time. To prevent animal exploitation and foster ethically desirable relationships with PTSD assistance dogs, their work conditions should not only minimise risks of harm but allow them to flourish and live a good life. Proposed guidelines include treating the dogs as agents, respecting their sustained dissent, providing sufficient rest, and allowing them to pursue their own interests. Furthermore, the work of PTSD assistance dogs should be enjoyable and beneficial for the involved canines, requiring force-free, non-aversive training and handling methods, and a strong bond with the human partner. Future research is needed to empirically investigate the welfare and ethical concerns highlighted in this paper, aiming to develop optimal practices that ensure PTSD assistance dog well-being.